2006
DOI: 10.1002/pds.1336
|View full text |Cite
|
Sign up to set email alerts
|

Nurses are increasingly involved in pharmacovigilance in Sweden

Abstract: Nurses, in their position as drug administrators who record signs and symptoms of the patients, play an increasingly important role for detection of suspected ADRs and are now contributing to a significant amount of the ADR reporting in Sweden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 19 publications
1
48
0
5
Order By: Relevance
“…Because nurses are in the ward at all times, it is most likely that any acute adverse drug reaction will first be observed by them, hence it is important that they participate in the spontaneous reporting scheme. In countries where nurses are already participating in the ADR reporting scheme, studies have shown that they indeed contribute positively towards the promotion of ADR reporting [7,24]. In this study, a majority of the nurses reported some form of ADR through the nurses daily report book and not the yellow card reporting scheme.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Because nurses are in the ward at all times, it is most likely that any acute adverse drug reaction will first be observed by them, hence it is important that they participate in the spontaneous reporting scheme. In countries where nurses are already participating in the ADR reporting scheme, studies have shown that they indeed contribute positively towards the promotion of ADR reporting [7,24]. In this study, a majority of the nurses reported some form of ADR through the nurses daily report book and not the yellow card reporting scheme.…”
Section: Discussionmentioning
confidence: 68%
“…The importance of healthcare workers in the area of spontaneous reporting of ADRs and development of ADR databases worldwide has been established in previous studies [7,8]. Previous studies from different regions in Nigeria have concentrated on the perception and practice of ADRs reporting among physicians only while excluding other cadres of healthcare workers [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…35 Estes profissionais são responsáveis pela administração e monitorização da terapêutica, particularmente nos idosos, estando numa posição privilegiada para identificar iatrogenia medicamentosa. [35][36][37][38][39] Apesar da nova legislação de Farmacovigilância permitir que tanto os profissionais de saúde como os utentes possam notificar suspeitas de reações adversas, a contribuição destes últimos tem sido residual. 40 Os utentes já estavam autorizados a notificar suspeitas de reações adversas há alguns anos noutros países, por exemplo na Dinamarca, na Holanda ou no Reino Unido.…”
unclassified
“…10,11 Previous studies reported a strong association between adverse drug reactions reporting and knowledge, attitude and practice of the healthcare professionals. 6,14,13,15 Therefore to establish and improve Pharmacovigilance program in any country, improving the knowledge, attitude and practice of health professional is essential.…”
mentioning
confidence: 99%